Infusing Additive Manufacturing Education with Applications: An Industry-Centric Approach - Wong, David S. K. (2016)
This paper details how Nanyang Polytechnic has applied industry-centric approach in training its students and industry personnel with relevant additive manufacturing technologies infused with real industry applications. It also briefs on its additive manufacturing journey of capability development, industry engagement and applied R&D activities over the last 15 years in tandem with the changing needs and manufacturing landscape in Singapore. It ends with case studies to demonstrate the impact, value-adding and benefits to industry of our additive manufacturing competencies.